Poligrafijos jmonės Lietuvoje 1918-1940 metais - Glosienė, Audronė (Knygotyra, 1992)
The article deals with the history of printing houses in Lithuania from 1918 to 1940. It covers the development of the printing industry after the First World War and the activities of the main printing houses during this twenty-year period. The State Printing House was established in 1918 and continued its work until 1928, when it was merged with the printing company Švyturys. This marked the beginning of the largest and most powerful printing company, Spindulys. Notable printing companies included Dirva, Žaibas, Varpas, and others. A significant number of printing houses were small private operations, many of which were not capable of printing books or periodicals. By 1939, there were 101 printing houses in Lithuania. The article concludes with a list of these printing houses.